2021
DOI: 10.3390/cells10071821
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolome Profiling Identifies Metabolic Subtypes of Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest cancers. Developing biomarkers for early detection and chemotherapeutic response prediction is crucial to improve the dismal prognosis of PDAC patients. However, molecular cancer signatures based on transcriptome analysis do not reflect intratumoral heterogeneity. To explore a more accurate stratification of PDAC phenotypes in an easily accessible matrix, plasma metabolome analysis using MxP® Global Profiling and MxP® Lipidomics was performed in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…As the downstream of systems biology, metabolomics can directly reflect the real life activities in pancreatic cancer cells, and any biological event associated with different phenotypes of pancreatic cancer must be presented in the changes of the metabolites. Mahajan et al identified three metabolic PDAC subtypes associated with distinct complex lipid patterns through PDAC plasma metabolome analysis 31 . Daemen et al applied an integrative analysis on transcriptomic and genomic data of glycolytic genes in PDA to identified two glycolytic and two nonglycolytic metabolic PDA subtypes 32 .…”
Section: Discussionmentioning
confidence: 99%
“…As the downstream of systems biology, metabolomics can directly reflect the real life activities in pancreatic cancer cells, and any biological event associated with different phenotypes of pancreatic cancer must be presented in the changes of the metabolites. Mahajan et al identified three metabolic PDAC subtypes associated with distinct complex lipid patterns through PDAC plasma metabolome analysis 31 . Daemen et al applied an integrative analysis on transcriptomic and genomic data of glycolytic genes in PDA to identified two glycolytic and two nonglycolytic metabolic PDA subtypes 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic profiling of 361 PDAC blood plasma samples identified three subtypes, with sphingolipid metabolism exhibiting differential enrichment between subtypes. Integrative analysis revealed that the 3 identified subtypes do not overlap with previously defined transcriptomic subtyping schemes and are not associated with clinical outcome (Mahajan et al, 2021). While identifying sphingolipid metabolites as potentially important biomarkers in PDAC, the utility of serum based metabolic profiling for patient stratification remains unclear.…”
Section: Pdac Blood Metabolomesmentioning
confidence: 91%
“…Best estimates suggest that CTCs exist at a ratio of one to ten cancer cells per 10 billion normal blood cells in a mL of blood ( Miller et al, 2010 ). CTCs are therefore typically enriched using phenotypic properties, such as size or density, or based on specific cell surface markers ( Lianidou et al, 2014 ; Martini et al, 2019 ; J.; Lee et al, 2019 ). Enrichment of CTCs by flow cytometry or microfluidic systems provides sufficient material for omic analysis including WGS ( Jiang et al, 2015 ), RNA-seq ( Yu et al, 2012 ), or single-cell sequencing ( Ting et al, 2014 ).…”
Section: Circulating Biomarkers In Pdacmentioning
confidence: 99%
“…Metabolomics quickly responds to public challenges: over 200 publications on COVID-19 metabolomics appeared in less than two years [214][215][216]. The spectrum of application of metabolic knowledge solo or as a part of multi-omics is broad: from microbial stains engineering [217] to precise and personalized health monitoring [218][219][220][221].…”
Section: Current Challenges and Prospects In Measuring Metabolitesmentioning
confidence: 99%